Home care utilization and costs in stage IV lung cancer: a Canadian public payer experience. (December 2014) - Mittmann, Nicole; Seung, Soo Jin; Liu, Ning; Porter, Joan; Leighl, Natasha; Trudeau, Maureen; Evans, William K; Earle, Craig
SUMMARY : Background: Lung cancer (LC) is a leading cause of morbidity and mortality and there is limited information on the type, quantity and cost of home care services (HCS) for LC.Aim: The objectives of this study include: identifying a stage IV LC cohort; determining the utilization and costs of HCS for the stage IV LC cohort; and comparing HCS utilization and costs by phase of disease.Methods: New cases of stage IV LC were extracted from a provincial cancer registry and linked to administrative datasets. HCS utilization and costs (2009 Canadian dollars [CAD]) for stage IV cases were determined from a public payer perspective and by disease phase.Results: There are 4616 stage IV LC patients who used HCS.. The mean number of HCS visits per 30 days was 7.7 and the mean cost per 30 days was CAD798 for terminal-phase patients.Conclusion: HCS costs for stage IV patients are less expensive than other health resources.